2008
DOI: 10.1143/ptps.174.145
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions and the Perfectness of Fluids

Abstract: We calculate the ratio η/s, the shear viscosity (η) to entropy density (s), which characterizes how perfect a fluid is, in weakly coupled real scalar field theories with different types of phase transitions. The resulting η/s behaviors agree with the empirical observations in atomic and molecular systems such as H 2 O, He and N. These behaviors are expected to be the same in N component scalar theories with an O(N ) symmetry. We speculate these η/s behaviors are general properties of fluid shared by QCD and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It has been proposed by the authors of [61] to use the shear viscosity over entropy density ratio as a signal of the critical end point(CEP). It has also been shown that η/s is suppressed near the critical temperature in the semi quark gluon plasma [62], and a cusp, a jump at T c and a shallow valley around T c in η/s can characterize first-, second-order phase transitions and crossover [63]. If the perturbative calculation based conclusion in [64] that small η/s implies large jet quenching parameter can be extended to strong coupled region, then we can expect that the temperature dependence behavior of jet quenching parameter can also contain the information of phase transition.…”
Section: Jhep06(2015)046mentioning
confidence: 99%
“…It has been proposed by the authors of [61] to use the shear viscosity over entropy density ratio as a signal of the critical end point(CEP). It has also been shown that η/s is suppressed near the critical temperature in the semi quark gluon plasma [62], and a cusp, a jump at T c and a shallow valley around T c in η/s can characterize first-, second-order phase transitions and crossover [63]. If the perturbative calculation based conclusion in [64] that small η/s implies large jet quenching parameter can be extended to strong coupled region, then we can expect that the temperature dependence behavior of jet quenching parameter can also contain the information of phase transition.…”
Section: Jhep06(2015)046mentioning
confidence: 99%
“…All known materials in nature by now satisfy this bound. More discussions on the universality and the bound can be found in [21,22,23,24,25,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of the SNO + experiment [37], placed in the SNOLAB in Canada, is the measurement of the neutrino-less double-beta decay (0ν − ββ) by means of 0.3% loading of scintillator with 800 kg of 130 Te (using natural Te) planned for spring 2016. The detec-tor will be filled with water in spring 2015, while with 1 kton of LAB scintillator in fall 2015.…”
Section: Solar Neutrinosmentioning
confidence: 99%